Replication and Meta-Analysis of 13,000 Cases Defines the Risk for Interleukin-23 Receptor and Autophagy-Related 16-Like 1 Variants in Crohn’s Disease - Lynn Cotterill; Debbie Payne; Scott Levison; John McLaughlin; Emma Wesley; Mark Feeney; Hilary Durbin; Simon Lal; Alistair Makin; Simon Campbell; Stephen A Roberts; Catherine O’Neill; et al. (Canadian Journal of Gastroenterology)
BACKGROUND/OBJECTIVE: Variants in the interleukin-23 receptor (IL23R) and the autophagy-related 16-like 1 (ATG16L1) genes have been associated with an increased risk of Crohn’s disease (CD). Both genes were identified through genome-wide association scans and subsequent studies have validated these associations. To assess the effect size of these variants, an independent case-control association study and meta-analysis were performed.